Communication, Leadership, and Motivation: Boosting Employee Morale Through Regression Analysis: Komunikasi, Kepemimpinan, dan Motivasi Kerja: Meningkatkan Semangat Karyawan Melalui Analisis Regresi - Achmad Taqwimul Khafid; Dewi Komala Sari (Academia Open, 2022)
This study aims to examine the influence of communication, leadership skills, and work motivation on employee morale in a private organization. The research utilized a saturated sampling method, with 67 respondents providing primary data. Multiple linear regression analysis was employed to analyze the data. The findings indicate that communication, leadership skills, and work motivation individually and collectively affect employee morale. The results highlight the significance of effective communication, strong leadership skills, and high work motivation in enhancing employee morale within organizations. These findings have important implications for managers and practitioners, emphasizing the importance of fostering positive communication, enhancing leadership skills, and promoting work motivation to boost employee morale in the workplace. Highlights: Effective communication, strong leadership skills, and high work motivation impact employee morale. Multiple linear regression analysis confirms the influence of communication, leadership skills, and work motivation on employee morale. Findings emphasize the importance of fostering positive communication, enhancing leadership skills, and promoting work motivation for boosting employee morale in organizations. Keywords: Communication, Leadership Skills, Work Motivation, Employee Morale, Multiple Linear Regression